Fully gapped superconducting state in Au2Pb: A natural candidate for topological superconductor. (16th February 2017) - Yu, Y. J.; Xu, Y.; Xing, Y.; Zhang, J.; Ying, T. P.; Hong, X. C.; Wang, M. X.; Zhang, X.; Jia, S.; Wang, J.; Li, S. Y.
Abstract: We measured the ultra-low-temperature specific heat and thermal conductivity of the Au2 Pb single crystal, a possible three-dimensional Dirac semimetal with a superconducting transition temperature . The electronic specific heat can be fitted by a two-band s -wave model, which gives the gap amplitudes Δ1 (0)/ k B T c  = 1.41 and Δ2 (0)/ k B T c  = 5.25. From the thermal conductivity measurements, a negligible residual linear term in zero field and a slow field dependence of at low field are obtained. These results suggest that Au2 Pb has a fully gapped superconducting state in the bulk, which is a necessary condition for topological superconductors if Au2 Pb is indeed one.